Research on uplink coverage enhancement of 5G network - Yuhua HU; Xinyan WANG; Bei LI (Dianxin kexue)
The 5G network frequency band is mostly high frequency band, which is rich in bandwidth resources, but the path loss and penetration loss are high, and the uplink coverage is relatively weak.If the low frequency band resources are introduced for uplink transmission, the cooperation of high and low frequency carriers will help to improve the uplink coverage.The link budget and coverage performance of 2.1 GHz and 3.5 GHz bands were analyzed, three uplink coverage enhancement schemes were compared, and the advantages and limitations of carrier aggregation scheme were analyzed.The result shows that carrier aggregation scheme is the optimal solution for 5G network uplink coverage enhancement.